2019
DOI: 10.1080/14620316.2019.1631128
|View full text |Cite
|
Sign up to set email alerts
|

Hail nets do not affect the efficacy of metamitron for chemical thinning of apple trees

Abstract: Hail nets reduce photosynthetically active radiation (PAR) and alter the environment under the netting in apple orchards. Thus, we investigated the effect of nets on the efficacy of metamitron, a short-term photosynthesis inhibitor used for fruit thinning. The objective of this study was to evaluate the effect of the netting and metamitron on thinning efficacy, yield, fruit quality and chlorophyll fluorescence in three apple cultivars. One or two metamitron applications at 165, 248 and 330 g (ai)/ha were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…Brevis reduced crop load, fruit set and number of fruits per tree. In most cases, the effect was higher with two applications of Brevis than with a single application, concurring with the observations of Dorigoni and Lezzer (2007), Gonzalez et al (2019a) and Stern (2014). Our results also suggest the sum effect of the number of applications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Brevis reduced crop load, fruit set and number of fruits per tree. In most cases, the effect was higher with two applications of Brevis than with a single application, concurring with the observations of Dorigoni and Lezzer (2007), Gonzalez et al (2019a) and Stern (2014). Our results also suggest the sum effect of the number of applications.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Byers (2003) concluded that low light conditions and periods of high night temperatures favour the abscission of fruitlets. Gonzalez et al (2019a) showed that night temperature was an important factor in explaining the efficacy of Brevis. When night temperatures are high, there is a resulting increase in the thinning effect (Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In all trials, the spraying of apple trees with chemical photosynthetic inhibitors induced fruit abscission, as also reported by Byers et al (1990). The application of Brevis ® reduced final fruit set, number of fruits per tree and crop load depending on the application rate, which concurs with the observations of Brunner (2014), Deckers et al (2010), Gonzalez et al (2019a), Mathieu et al (2016 and . Final fruit set, number of fruits per tree, crop load and yield showed differences between Gala and Fuji cultivars because product susceptibility differs according to cultivar because the meteorological conditions differed between years.…”
Section: Discussionsupporting
confidence: 89%
“…which crop load and final fruit set were significantly reduced. These results again concurring with earlier observations made by McArtney et al (1996), Brunner (2014), Gonzalez et al (2019a) and Maas and Meland (2016). Fruit size and fruit color distribution improved with yield reduction, also concurring with earlier observations of Bergh (1990), Dorigoni and Lezzer (2007) and Lafer (2010), as did the various % values of the fruit harvested at first pick (% of yield >70 mm, >75 mm and >60% blush area), as also reported by Mathieu et al (2016).…”
supporting
confidence: 92%
“…Orchard netting is a technique that has become widespread in apple production to prevent damage from adverse climatic events, such as sunburn in countries such as Chile, South Africa, the United States, and Australia [1][2][3][4], hail in countries such as Germany, Italy, and Spain [5][6][7], and insect attacks such as codling moth in countries such as Italy, France, and Canada [6,8,9]. This wide range of uses of netting in apple trees implies the adoption of different installation systems and net designs, differentially impacting microclimatic conditions of light, temperature, relative humidity, and wind speed [9][10][11], and with a consequent effect on plant physiological responses, such as leaf gas exchange, water relations, tree growth, floral development, and fruit quality traits [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%